The neurotoxin 1-methyl-4-phenylpyridinium (MPP+) alters hippocampal excitatory synaptic transmission by modulation of the GABAergic system - Huang, YuYing; Chen, JunFang; Chen, Ying; Zhuang, YingHan; Sun, Mu; Behnisch, Thomas (Frontiers in Cellular Neuroscience, 2015)
The neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) induces Parkinson’s disease (PD)-like symptoms following administration to mice, monkeys and humans. A common view is that MPTP is metabolized to 1-methyl-4-phenylpyridinium ion (MPP+) to induce its neurodegenerative effects on dopaminergic neurons in the substantia nigra. Moreover, the hippocampus contains dopaminergic fibers, which are projecting from the ventral tegmental area, substantia nigra and pars compacta and contain the whole machinery required for dopamine synthesis making them sensitive to MPTP and MPP+. Here we present data showing that acute bath-application of MPP+ elicited a dose-dependent facilitation followed by a depression of synaptic transmission of hippocampal Schaffer collaterals-CA1 synapses in mice. The effects of MPP+ were not mediated by D1/D5- and D2-like receptor activation. Inhibition of the dopamine transporters (DAT) did not prevent but increased the depression of excitatory postsynaptic field potentials. In the search for a possible mechanism, we observed that MPP+ reduced the appearance of polyspikes in population spikes recorded in str. pyramidale and increased the frequency of miniature inhibitory postsynaptic currents. The acute effect of MPP+ on synaptic transmission was attenuated by co-application of a GABAA receptor antagonist. Taking these data together, we suggest that MPP+ affects hippocampal synaptic transmission by enhancing some aspects of